Prevalence of Cannabis Lifetime Use in Iranian High School and College Students - Milad Nazarzadeh MSc; Zeinab Bidel MSc; Alireza Mosavi Jarahi PhD; Keihan Esmaeelpour MD; Walieh Menati MSc; Ali Asghar Shakeri MSc; Rostam Menati MSc; Sattar Kikhavani PhD; Kourosh Saki PhD (American Journal of Men's Health, 2015)
Cannabis is the most widely used substance in the world. This study aimed to estimate the prevalence of cannabis lifetime use (CLU) in high school and college students of Iran and also to determine factors related to changes in prevalence. A systematic review of literature on cannabis use in Iran was conducted according to MOOSE guideline. Domestic scientific databases, PubMed/Medline, ISI Web of Knowledge, and Google Scholar, relevant reference lists, and relevant journals were searched up to April, 2014. Prevalences were calculated using the variance stabilizing double arcsine transformation and confidence intervals (CIs) estimated using the Wilson method. Heterogeneity was assessed by Cochran’s Q statistic and I 2 index and causes of heterogeneity were evaluated using meta-regression model. In electronic database search, 4,000 citations were retrieved, producing a total of 33 studies. CLU was reported with a random effects pooled prevalence of 4.0% (95% CI = 3.0% to 5.0%). In subgroups of high school and college students, prevalences were 5.0% (95% CI = 3.0% to −7.0%) and 2.0% (95% CI = 2.0% to −3.0%), respectively. Meta-regression model indicated that prevalence is higher in college students (β = 0.089, p < .001), male gender (β = 0.017, p < .001), and is lower in studies with sampling versus census studies (β = −0.096, p < .001). This study reported that prevalence of CLU in Iranian students are lower than industrialized countries. In addition, gender, level of education, and methods of sampling are highly associated with changes in the prevalence of CLU across provinces.